2011
DOI: 10.1088/0004-6256/141/4/111
|View full text |Cite
|
Sign up to set email alerts
|

Far-Infrared Imaging of Post-Asymptotic Giant Branch Stars and (Proto)-Planetary Nebulae With the Akari Far-Infrared Surveyor

Abstract: By tracing the distribution of cool dust in the extended envelopes of post-AGB stars and (proto)planetary nebulae ((P)PNe) we aim to recover, or constrain, the mass loss history experienced by these stars in their recent past. The Far-Infrared Surveyor (FIS) instrument on board the AKARI satellite was used to obtain far-infrared maps for a selected sample of post-AGB stars and (P)PNe. We derived flux densities (aperture photometry) for 13 post-AGB stars and (P)PNe at four far-infrared wavelengths (60, 90, 140… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…They interpreted that the far-IR variability in its infrared flux might occur due to recent mass-loss event(s) or evolution of the CSPN. Following the report of Cox et al (2011) and the dust mass ∼4.0(-5) M ⊙ co-existing with the ionized gas by the IRAS data in 1980s, we estimate the dust mass to be 2(-5) M ⊙ in 2006-2007, which is comparable to our derived dust mass of 3.79(-5) M ⊙ within the ionized gas.…”
Section: ′′supporting
confidence: 80%
See 2 more Smart Citations
“…They interpreted that the far-IR variability in its infrared flux might occur due to recent mass-loss event(s) or evolution of the CSPN. Following the report of Cox et al (2011) and the dust mass ∼4.0(-5) M ⊙ co-existing with the ionized gas by the IRAS data in 1980s, we estimate the dust mass to be 2(-5) M ⊙ in 2006-2007, which is comparable to our derived dust mass of 3.79(-5) M ⊙ within the ionized gas.…”
Section: ′′supporting
confidence: 80%
“…These estimated values are consistent with our derived m g and m d when we stopped the model at r ib . On the dust, Cox et al (2011) found that the AKARI far-IR flux densities are by a factor two lower than predicted from the IRAS data. They interpreted that the far-IR variability in its infrared flux might occur due to recent mass-loss event(s) or evolution of the CSPN.…”
Section: ′′mentioning
confidence: 72%
See 1 more Smart Citation
“…This is primarily true for the physical processes that shape the complex structure of PPN envelopes. Images taken with the Hubble Space Telescope [4,5] and during space IR missions [6] are rarely spherical. Central stars are usually surrounded by envelopes in the form of extended haloes, arcs, lobes, and tori.…”
Section: Introductionmentioning
confidence: 99%
“…Infrared surveys (e.g., 2MASS, IRAS, and AKARI) have contributed to the study of objects in the late AGB and early post-AGB stages, providing the first insights into this short transition phase (e.g., García-Lario et al 1997;Jiménez-Esteban et al 2006;Cox et al 2011). Recently, Ramos-Larios et al (2009);Ramos-Larios et al (2012, hereafter RL09 and RL12, respectively) have investigated a sample of heavily obscured post-AGB and PNe candidates selected according to their IRAS colors and the lack of an optical counterpart (Suárez et al 2006) using near-IR JHK and Spitzer IRAC GLIMPSE images, and MSX, AKARI, and IRAS photometric data.…”
Section: Introductionmentioning
confidence: 99%